2019
DOI: 10.22159/ajpcr.2020.v13i3.36575
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Vestibular Stimulation in Children With Developmental Coordination Disorder

Abstract: Objectives: The objectives of this study were to find out the effects of vestibular stimulation in developmental coordination disorder (DCD) children. Methodology: Thirty children (n=30) were screened using the DCD questionnaire (DCDQ). After baseline screening among the 30 children, 15 were confirmed as suspects of DCD. Vestibular stimulation was given for all the 15 children. Results: It is revealed that the motor coordination was improved significantly in children with DCD. Conclusion: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Future research was in need to analyze the relationships between motor skill defects and mood impairments in an adolescent with DCD. Clearly, this study has identified that adults with DCD experience motor impairments and they will never outgrow their symptoms and experience stress, anxiety, and depression [8][9][10]. Further literature should document the mood impairments in DCD and the existence of individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…Future research was in need to analyze the relationships between motor skill defects and mood impairments in an adolescent with DCD. Clearly, this study has identified that adults with DCD experience motor impairments and they will never outgrow their symptoms and experience stress, anxiety, and depression [8][9][10]. Further literature should document the mood impairments in DCD and the existence of individual differences.…”
Section: Discussionmentioning
confidence: 99%